Titel prent: De makkelijke wet : "Kerel, ik zit er zoo tusschen. Mijn voorraad wordt te groot..." - Hahn, Albert
Titel prent: De makkelijke wet : "Kerel, ik zit er zoo tusschen. Mijn voorraad wordt te groot...".